2017
DOI: 10.1007/s11293-016-9523-5
|View full text |Cite
|
Sign up to set email alerts
|

Does the Median Voter or Special Interests Determine State Highway Expenditures? Recent Evidence

Abstract: Using cross-sectional data from fifty states of the United States and the District of Columbia for two different time periods, this paper examines the degree to which special interests or the median voter determines state highway expenditures. In addition to finding that previous estimates of the determinants of state highway expenditures are robust, we find that that special interests that were important in 1984 were no longer significant nearly 20 years later. Like the previous literature, we conclude that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Recent work byHall and Pokharel (2017) found that the median voter model continues to outperform the special interest model with 2013 state-level data.3 The empirical specification in Gamkhar and Ali (2007) controls for regional, rather than state fixed-effects.4 Whereas each state has two senators, the number of House members ranges from one at-large member -Alaska, Delaware, Montana, North Dakota, South Dakota, Vermont, and Wyoming -to fifty-three representatives in California. Furthermore, the unit of observation is the state, meaning that there are not enough degrees of freedom to include an appropriate control function.…”
mentioning
confidence: 99%
“…Recent work byHall and Pokharel (2017) found that the median voter model continues to outperform the special interest model with 2013 state-level data.3 The empirical specification in Gamkhar and Ali (2007) controls for regional, rather than state fixed-effects.4 Whereas each state has two senators, the number of House members ranges from one at-large member -Alaska, Delaware, Montana, North Dakota, South Dakota, Vermont, and Wyoming -to fifty-three representatives in California. Furthermore, the unit of observation is the state, meaning that there are not enough degrees of freedom to include an appropriate control function.…”
mentioning
confidence: 99%